Identification methods and susceptibility of Candida spp. isolates in patients with COVID-19: Narrative review - Sánchez-Pérez, Jorge Andrés (2025)
Objetive: This integrative review with a descriptive approach aimed to describe the available scientific information on the methods of antifungal identification and susceptibility used to characterize Candida isolates from blood cultures in patients diagnosed with COVID-19. Methods: A systematic search of primary publications was conducted in databases including MEDLINE/PubMed and the Cochrane Library. Specific inclusion and exclusion criteria were established to select studies conducted between 2020 and 2023. Case reports and series, as well as retrospective and prospective analytical studies, were included to describe molecular methods for the identification of Candida species, antifungal susceptibility testing, and the assessment of clonality and resistance genes. Our review process was based on the Whittemore and Knafl model. Results: A total of 446 studies were identified, of which 18 met the criteria for detailed analysis. These studies were evaluated for their level of evidence and quality, and relevant information was extracted regarding the microbiological characterization of Candida isolates and their relationship with COVID-19 coinfection. The studies employed a variety of methodologies, including proteomic and molecular identification techniques, and reported multidrug-resistant Candida isolates, particularly Candida auris. Conclusion: This integrative review provided insights into the species identification, susceptibility, and antifungal resistance genes associated with Candida isolates in patients diagnosed with COVID-19, highlighting the importance of a multidisciplinary approach to address this emerging clinical issue.